2016
DOI: 10.1155/2016/6917950
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanosized LaCoO3through Calcination of a Hydrothermally Synthesized Precursor

Abstract: A method for obtaining nanosized LaCoO3crystals from calcination of a precursor powder synthesized by a hydrothermal route is reported. Details concerning the evolution of the microstructure and formation mechanism of the perovskite phase were studied by powder X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, Raman spectroscopy, and thermal analysis. It was found that the morphology of the sample progressively turns from a mix of fibers and rods to interconnected nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…The prepared catalyst had a pure perovskite structure and orthogonal crystal. The XRD spectra of the supported catalyst LaCoO 3 /CeO 2 prepared by impregnation showed not only obvious characteristic diffraction peaks of LaCoO 3 perovskite structure but also characteristic peaks of CeO 2 at 29.08°, 33.04°, and 56.51°, corresponding to the standard card of CeO 2 (PDF#1-800) [ 24 ]. This result confirmed that an LaCoO 3 perovskite-type structure was formed on the surface of the CeO 2 support, and the crystal forms of the support and active component were not destroyed.…”
Section: Resultsmentioning
confidence: 99%
“…The prepared catalyst had a pure perovskite structure and orthogonal crystal. The XRD spectra of the supported catalyst LaCoO 3 /CeO 2 prepared by impregnation showed not only obvious characteristic diffraction peaks of LaCoO 3 perovskite structure but also characteristic peaks of CeO 2 at 29.08°, 33.04°, and 56.51°, corresponding to the standard card of CeO 2 (PDF#1-800) [ 24 ]. This result confirmed that an LaCoO 3 perovskite-type structure was formed on the surface of the CeO 2 support, and the crystal forms of the support and active component were not destroyed.…”
Section: Resultsmentioning
confidence: 99%
“…The precursor in this case was identified to be [Co 2 O 3 ·2La(NO 3 ) 3 ·3H 2 O], which, after heat treatment at 500 °C, yielded the LaCoO 3 coating. This temperature is significantly lower than that used for the calcination of LaCoO 3 powders obtained by solid-state reaction (1000 °C [ 38 ]) hydrothermal synthesis (850 °C [ 39 ]) methods.…”
Section: Electrodeposition Technology For the Fabrication Of Sofc Air Electrodes With Increased Performancementioning
confidence: 99%
“…In other conditions, preferred distortions orthorhombic, rhombohedral, and to a lesser extent tetragonal, mono, or triclinic perovskites will appear [8]. Although, it is difficult to synthesize these materials in their pure bulk form, due to the stabilization of Ni(III) and either oxygen pressure and/or high temperatures of ~950 ºC are necessary [1,2,8,9], it is possible to prepare these perovskite materials comparatively in the pure form either by modified conventional ceramic, co-precipitation, sol-gel, hydrothermal, auto-combustion and also by other modern techniques like pulse laser, spray pyrolysis techniques for thin films. LaNiO 3 and LaCoO 3 have rhombohedrally distorted perovskite structures at room temperature [3,4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%